From Crisis to Credibility: The Need for Quality Jobs for Young People. Issue 2 (December 2013) - Higgins, James; Porcaro, Giuseppe
The youth unemployment crisis that has unravelled in Europe since 2008 has dramatically impacted the lives of young people. The transition from education to employment has become increasingly difficult. Not only is the rate of youth unemployment at record levels, but young people are more likely to be in poorly paid and precarious jobs. As a result, the number of young people at risk of poverty and social exclusion has been growing steadily throughout Europe. This article aims to contextualise youth unemployment in terms of the changes to the European economy and European social model over the past 20 years, and to propose areas that need to be addressed in order to reduce unemployment and positively impact the lives of young people in Europe.